Pengaruh Level Protein, Vitamin A dan Vitamin E terhadap Pertambahan Bobot Badan dan Beberapa Fungsi Reproduksi Tikus Putih (Rattus norvegicus) - . Yudi; A Parakkasi (Faculty of Animal Science, Bogor Agricultural University, 2005)
Protein has the role in the development of physiological structure and body immunity system. Reproductive hormones, gametogenesis and fetus development are very much affected by the content of protein, vitamin A and E. Vitamin A is known to have a role in the integrity of epithel tissue, thus it has a great effect on the process of gametogenesis and embryogenesis. Vitamin E is recognized as an anti-sterility vitamin because of its important role as an intercellular antioxidant, in absorbing and storing vitamin A. This research was intended to determine the effect of protein content (15%, 18% and 21%), vitamin A (2000 IU/kg of feed), and vitamin E (30 mg/kg of feed) on body weight and some characteristics of reproduction of white mice (Rattus novergicus). The reproduction characteristics observed on female were the litter size and their body weight at birth, whereas those on male were fertility and morphology of spermatozoa. The research results showed that there were some effects of protein, vitamin A and E on increased body weight of female. The best result with a significant change (P